Tantangan Manajemen Dakwah Forum Muslimah Dakwah Kampus Daerah Bone dalam Menghadapi Dinamika Kampus Modern - Hatimah, Husnul; Qudratullah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
Da'wah is a vital activity in conveying Islamic teachings to the public, including within university settings. The campus serves as a strategic environment for shaping students' Islamic character, as they play a key role in upholding societal values. Amidst the rapid development of the times and technological advancements, campus-based da'wah must adapt to social dynamics and the evolving mindset of students, particularly in the digital era. In this context, the Forum Muslimah Dakwah Kampus Indonesia (FMDKI) in the Bone region plays a crucial role in promoting Islamic values among university students across campuses in Bone Regency. This study aims to analyze the challenges and solutions related to da'wah management within FMDKI Bone, focusing on its operations across local campuses. The primary emphasis is placed on aspects of da'wah management, including internal communication among leaders, the adaptation of da'wah activities to contemporary developments, and the difficulty of encouraging active participation among da'wah participants. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews with FMDKI Bone administrators and members. The findings reveal that the main challenges faced by the organization include a lack of effective communication among leaders, difficulties in tailoring da'wah methods to engage Generation Z audiences, and the need for continuous renewal of da'wah content to remain relevant in a changing world. This study is expected to contribute to the development of more effective da'wah management strategies in the digital age, with the aim of nurturing Islamic character among university students.